1989
DOI: 10.1021/ja00196a003
|View full text |Cite
|
Sign up to set email alerts
|

Production of hydrated metal ions by fast ion or atom beam sputtering. Collision-induced dissociation and successive hydration energies of gaseous copper+ with 1-4 water molecules

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 3 publications
13
121
2
Order By: Relevance
“…However, calculated structures for the stable, hydrated hydroxyuranyl complexes do not appear to support this (vide infra). It is worthwhile noting that the relative ordering of the rate constants mirrors earlier studies of hydrate thermodynamics for first row transition metal monocations M ϩ , which showed that the bond energy for the second water molecule was Ն that of the first [43][44][45][46][47][48]; since this trend was not observed for alkali metals, it was rationalized in terms of orbital rehybridization. Since orbital rehybridization is also significant in the uranyl system [41], measurement of bond energies for the three H 2 O molecules attached to (UO 2 OH) ϩ is needed, but cannot be accomplished using the present experimental setup.…”
Section: Resultssupporting
confidence: 69%
“…However, calculated structures for the stable, hydrated hydroxyuranyl complexes do not appear to support this (vide infra). It is worthwhile noting that the relative ordering of the rate constants mirrors earlier studies of hydrate thermodynamics for first row transition metal monocations M ϩ , which showed that the bond energy for the second water molecule was Ն that of the first [43][44][45][46][47][48]; since this trend was not observed for alkali metals, it was rationalized in terms of orbital rehybridization. Since orbital rehybridization is also significant in the uranyl system [41], measurement of bond energies for the three H 2 O molecules attached to (UO 2 OH) ϩ is needed, but cannot be accomplished using the present experimental setup.…”
Section: Resultssupporting
confidence: 69%
“…It is well known that Cu + forms very strongly bonded dicoordinated linear complexes and that the first two bond energies Cu + L and LCu + L are approximately equal and much higher than those with additional ligands as mentioned above [7][8][9][10][11][12][13][14][15]. Indeed, recent experimental data for H 2 O, NH 3 , (Me) 2 O, MeCN, and acetone indicate that the second binding energy is identical to the first one [7][8][9][10].…”
Section: Comparison Of Binding Energies Of Cu + Between the First Andmentioning
confidence: 95%
“…In these studies, the L 2 Cu + complexes rather than LCu + were choosen owing to experimental convenience. Since the first two bond energies Cu + L and CuL + L are approximately equal and much higher than those observed with additional ligands [7][8][9][10][11][12][13][14][15], the special stability of L 2 Cu + enables the measurements of the exchange equilibria. Although these results may provide somewhat restricted information, they are very valuable because they deal with the first two strongest bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…They dealt with different aspects of cation-water interactions: with energetics and spectra, coordination numbers, and geometries. In particular, it has been shown that the binding energies change significantly with both the metal ion and the number of ligands [2,5,6,. They generally decrease with the number of water molecules.…”
Section: Introductionmentioning
confidence: 99%